Aristotle and the People: Vernacular Philosophy in Renaissance Italy - Sgarbi, Marco (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
The essay focuses on vernacular Aristotelianism in Renaissance Italy, which began to gain currency in the 1540s, just as the vernacular was beginning to establish itself as a language of culture and the Counter-Reformation was getting underway. With over three hundred printed and manuscript works, the statistics of this phenomenon are impressive. Even so, the vulgarization of Aristotle in the Italian Renaissance has never received the scholarly attention it deserves. The paper examines (1) the identity of the recipients of Aristotle’s vulgarizations, (2) the meaning of the process of vulgarization, and (3) the conception of knowledge that such writings brought to the culture of the Cinquecento. The purpose is to show that (1) vernacular renderings of Aristotle’s works were aimed at the “people,” including “idiots” (men lacking culture or knowledge of Latin), “simpletons,” “ignorants,” and “illiterates” as well as princes, men of letters, women, and children, (2) vulgarization was not simply a matter of disseminating, simplifying, and trivializing knowledge, and (3) vulgarization upheld the notion of widespread knowledge.